The role of service fairness, service experience, and customer engagement in driving repurchase intention: Evidence from Thailand’s aesthetic industry - Siriudomset, Watcharit; Udomratanamanee, Theerakorn; Srising, Peerapat; Tangsophon, Suphicha (International Journal of Innovative Research and Scientific Studies, 2025)
The aesthetic industry in Thailand has experienced rapid growth, blending cultural heritage with modern wellness trends to attract both local and international consumers. Despite its expansion, limited research has examined the psychological and experiential drivers behind customer behavior in this sector. This study investigates the impact of service fairness, service experience, and customer engagement on repurchase intention, applying Equity Theory to understand how perceptions of fairness influence loyalty outcomes. Drawing on validated frameworks, the study employed a quantitative approach using a structured questionnaire administered to 528 aesthetic service consumers in Thailand. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Measurement model assessments confirmed reliability, convergent, and discriminant validity. Structural analysis revealed that service fairness significantly influences both customer engagement and service experience, which in turn predict repurchase intention. Mediation analysis confirmed that both service experience and engagement mediate the relationship between service fairness and repurchase intention. The findings emphasize the importance of emotional and relational value in customer loyalty. Fair treatment enhances trust and engagement, while positive service experiences foster repurchase behavior. Practically, the study suggests that aesthetic service providers should prioritize fairness, transparent communication, and emotionally engaging service delivery. This study contributes to the literature by extending service and relationship marketing theories into the context of aesthetic services. Limitations include the cross-sectional design and focus on a specific industry, which may restrict generalizability. Future research is encouraged to explore longitudinal effects, include comparative industry analysis, and consider demographic or cultural moderators.